2019
DOI: 10.1002/14651858.cd013513
|View full text |Cite
|
Sign up to set email alerts
|

Biologics for chronic rhinosinusitis

Abstract: Biologics for chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…Studies with mepolizumab have shown a significant reduction in patients’ need for surgery and an improvement in symptoms [ 5 , 124 , 125 ]. A Cochrane review summarized that mepolizumab may improve both disease-specific and generic health-related quality of life (HRQL), yet its effect to reduce surgery or improve nasal polyp score is uncertain [ 126 ]. At the moment, phase 3 RCTs are ongoing for both benralizumab and mepolizumab, altogether with over 800 patients with severe CRSwNP [ 41 ].…”
Section: Monoclonal Antibodies and Treatment Of Airway Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with mepolizumab have shown a significant reduction in patients’ need for surgery and an improvement in symptoms [ 5 , 124 , 125 ]. A Cochrane review summarized that mepolizumab may improve both disease-specific and generic health-related quality of life (HRQL), yet its effect to reduce surgery or improve nasal polyp score is uncertain [ 126 ]. At the moment, phase 3 RCTs are ongoing for both benralizumab and mepolizumab, altogether with over 800 patients with severe CRSwNP [ 41 ].…”
Section: Monoclonal Antibodies and Treatment Of Airway Diseasesmentioning
confidence: 99%
“…It also diminished the need for rescue treatment with systemic corticosteroids and sinus surgery [ 128 ]. A Cochrane review summarizes that dupilumab has been shown to improve disease-specific HRQL compared to placebo, and it might improve symptoms and generic HRQL and reduce the need for further surgery [ 126 ]. Moreover, there is no evidence of an increased risk of serious adverse events; however, there may be little or no difference in the risk of nasopharyngitis [ 126 ].…”
Section: Monoclonal Antibodies and Treatment Of Airway Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinosinusitis (acute or chronic) is a common disease that affects patients' quality of life. 1 Common symptoms are nasal blockage and discharge, though some patients may also experience postnasal drip, facial pain, loss of smell, or sleep disturbance. [2][3][4] The prevalence of acute rhinosinusitis ranges between 1500 to 4000 per 100 000 population, while the incidence of chronic rhinosinusitis is around 1800 to 2300 per 100 000 population.…”
Section: Introductionmentioning
confidence: 99%
“…Rhinosinusitis (acute or chronic) is a common disease that affects patients' quality of life 1 . Common symptoms are nasal blockage and discharge, though some patients may also experience postnasal drip, facial pain, loss of smell, or sleep disturbance 2‐4 .…”
Section: Introductionmentioning
confidence: 99%